2005
DOI: 10.1111/j.1600-0609.2005.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported quality of life in elderly patients with aggressive non‐Hodgkin's lymphoma treated with CHOP chemotherapy

Abstract: We studied the impact of CHOP chemotherapy on the quality of life (QoL) of elderly patients with aggressive non-Hodgkin's lymphoma (NHL). 132 patients aged 65 or older, who participated in a randomized, multicenter trial, completed QoL questionnaires (EuroQol-5D, EORTC QLQ-C30 and MFI-20) on 8 predefined time-points before, during and following treatment. At baseline, QoL was significantly better on almost all dimensions in patients with a lower compared to patients with a higher age-adjusted International Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 20 publications
2
46
0
3
Order By: Relevance
“…A escassez de estudos na literatura que avaliam a qualidade de vida de idosos em quimioterapia dificulta uma comparação direta com o presente estudo. 17 A piora do domínio "desempenho físico", aqui encontrada, também já havia sido descrita por Doordjuin et al 9 em pacientes idosos pouco sintomáticos com linfoma não-Hodgkin agressivo, quando se avaliou o efeito da quimioterapia por doença avançada/sintomática. Observou-se piora no desempenho físico naqueles que eram pouco sintomáticos; já para aqueles com mais sintomas, o desempenho físico melhorou após o início da quimioterapia.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A escassez de estudos na literatura que avaliam a qualidade de vida de idosos em quimioterapia dificulta uma comparação direta com o presente estudo. 17 A piora do domínio "desempenho físico", aqui encontrada, também já havia sido descrita por Doordjuin et al 9 em pacientes idosos pouco sintomáticos com linfoma não-Hodgkin agressivo, quando se avaliou o efeito da quimioterapia por doença avançada/sintomática. Observou-se piora no desempenho físico naqueles que eram pouco sintomáticos; já para aqueles com mais sintomas, o desempenho físico melhorou após o início da quimioterapia.…”
Section: Discussionunclassified
“…Isto demonstra que o efeito do tratamento, no desempenho físico, talvez seja benéfico para aqueles que tenham muitos sintomas da doença antes de iniciar a quimioterapia. 9 Esse efeito pode ter ocorrido nos sete (22,6%) pacientes portadores de neoplasia de pulmão que tiveram as médias de desempenho físico aumentadas, quando comparados os momentos "antes" e "depois" da quimioterapia. 9,17 Quando se avaliam as médias dos escores do domínio "estado de saúde geral/QV" do EORTC QLQ-C30 nos momentos "antes" e "depois", evidencia-se que não houve modificação, exceto para a neoplasia da próstata, que piorou de maneira significativa.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Results from the study showed that total costs discounted 3% in the CHOP-only treatment arm were lower ( 28,782) than that in the R-CHOP treatment arm ( 41,952) mainly due to the added drug cost of rituximab. However, the CHOP-only group demonstrated 3.59 QALYs whereas R-CHOP resulted in 4.66 QALYs.…”
Section: Studies Using Cost-utility Analysismentioning
confidence: 99%
“…QALYs were based on a study [24] which only looked at elderly NHL patients, even though younger patients were also included by Groot and colleagues. Using weighted averages of the utilities, the authors assigned scores based on initial treatment (0.60), progression-free disease (0.81), disease progression (0.60), or death (0.00).…”
Section: Studies Using Cost-utility Analysismentioning
confidence: 99%